Study of Value Chain of Indian Textile Handicrafts : A Case of Lucknow Chikankari - Singh, Jagriti; Srivastava, Alpana; Awasthi, Maya Kant (Prabandhan: Indian Journal of Management, 2018)
This paper studied different types of existing value chain models of Lucknowi Chikankari in context of the value chain model given by Porter (1985). Chikankari being an unorganized sector, the paper focused on the primary activities of Porter’s value chain model. To have an in-depth understanding of different models and to highlight differences between them, field-based qualitative research in an informative manner seemed appropriate. Therefore, multiple-case-based research methodology was adopted for data collection and analysis. The study identified and outlined the prevalent three types of value chain models as traditional, contemporary, and mixed with respect to the primary activities of the value chain. The findings drew a comparison between various types of value chains prevalent in the industry, highlighting the relevant differences among them and suggesting the best suited one in artisans’ interests. The study stated that the interventions that can be undertaken through collaboration of government, private organizations, and NGOs to improve the situation of artisans and contribute towards sustainability of the craft can be achieved by improvements and modifications in design and execution of activities. The suggestions and recommendations were made pertaining to eliminating the involvement of middlemen to reduce the cycle size and increase artisans’ wages. The government should work towards educating the progressive artisans in e-commerce and linking them to e-commerce portals. The study suggested that for development of organizations, government, marketers, and producers (artisans), evolving a sustainable value chain in the interest of artisans and the industry is required.